How Leverage, Profitability, Profit Persistence, Capital Intensity, and Litigation Risk Influence Accounting Conservatism - Widiatmoko, Wahyu Bagas; Achyani, Fatchan (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the effect of Leverage, Profitability, Earnings Persistence, Capital Intensity, and Litigation Risk on Accounting Conservatism in technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research approach used is quantitative with multiple regression analysis to determine the effect of each independent variable on the dependent variable. The results of the study indicate that Leverage, Earnings Persistence, and Capital Intensity do not affect accounting conservatism. This indicates that the level of debt, profit stability, and the size of fixed assets are not determining factors in the application of the principle of conservatism by companies. On the contrary, Profitability and Litigation Risk have a significant effect on accounting conservatism. The higher the level of profitability, the lower the company's tendency to apply conservatism. Meanwhile, the greater the risk of litigation faced, the higher the application of accounting conservatism as a form of prudence. These findings imply that external factors, such as legal risk, play a more significant role in driving corporate conservative practices than internal factors, such as financial structure and assets.